Gendered symbolism as a medium to negotiate power as evidenced in the furnished Viking burials of Ireland - Wade, Christina (Trinity College (Dublin, Ireland). Department of History, 2017)
This thesis is an examination of the gendered symbolism of grave goods as evident in the furnished burials of Ireland. The practice in Ireland is dated to between 840 and 950 CE, a period also marked by violence and warfare between the native Irish and the Viking settlers. The conflicts inherent in this time period gave rise to specific cultural responses from the Vikings. A central part of this thesis' examination was the study of how this came to impact on burial. In order to conduct this research the category of gender was utilized, as well as the tool of deconstruction. The use ofthese, as well as feminist theories, enabled this thesis to conduct research into femininities and masculinities, and therefore allowed it to conclude that these nuanced expressions of gender were indeed utilized by the Vikings in burial symbolism and that gendered forms of power, myriad and nuanced, were deployed as a method to negotiate power.
Keywords: Medieval History, Ph.D.; Ph.D. Trinity College Dublin, 2017